Computational intelligence for genetic association study in complex diseases: review of theory and applications. (26th March 2009) - Kelemen, Arpad; Vasilakos, Athanasios V.; Liang, Yulan
Comprehensive evaluation of common genetic variations through association of SNP structure with common complex disease in the genome-wide scale is currently a hot area in human genome research thanks for the recent development of the Human Genome and HapMap Projects. Computational science, which includes computational intelligence, has recently become the third method of scientific enquiry besides theory and experimentation. There have been fast growing interests in developing and applying computational intelligence in disease mapping using SNP and haplotype data. This review provides coverage of recent developments of theory and applications in computational intelligence for complex diseases in genetic association study.